(untitled) (Agora for Physical Education and Sport, 2020)
The natural environment has some features that make it different, allowing the realization of activities aimed at the global development of the participants. However, it requires in advance planning and the use of appropriate educational methodology. This dual premise was the basis for this study. The main objective was to look at the benefits for the students that took part in a specific educational practice carried out in the natural environment through experiential methodology. Specifically, we analyzed learning improvement and the development of personal and social skills. The participants were 69 students of the subject Activities in the Natural Environment, from the Faculty of Physical Activity and Sport Sciences-INEF of Madrid. Two questionnaires were applied, one before and the other at the end of the training practice. These instruments were complemented by a field notebook and an observation sheet. Results showed improvements in learning acquisition and in interpersonal relations, and an increase in motor autonomy. In short, the educational practice contributed to the integral development of the participants.